Fusion product losses due to fishbone instabilities in deuterium JET plasmas. (8th November 2017) - Kiptily, V.G.; Fitzgerald, M.; Goloborodko, V.; Sharapov, S.E.; Challis, C.D.; Frigione, D.; Graves, J.; Mantsinen, M.J.; Beaumont, P.; Garcia-Munoz, M.; Perez von Thun, C.; Rodriguez, J.F.R.; et al.
Abstract: During development of a high-performance hybrid scenario for future deuterium–tritium experiments on the Joint European Torus, an increased level of fast ion losses in the MeV energy range was observed during the instability of high-frequency n = 1 fishbones. The fishbones are excited during deuterium neutral beam injection combined with ion cyclotron heating. The frequency range of the fishbones, 10–25 kHz, indicates that they are driven by a resonant interaction with the NBI-produced deuterium beam ions in the energy range ⩽120 keV. The fast particle losses in a much higher energy range are measured with a fast ion loss detector, and the data show an expulsion of deuterium plasma fusion products, 1 MeV tritons and 3 MeV protons, during the fishbone bursts. An MHD mode analysis with the MISHKA code combined with the nonlinear wave-particle interaction code HAGIS shows that the loss of toroidal symmetry caused by the n = 1 fishbones affects strongly the confinement of non-resonant high energy fusion-born tritons and protons by perturbing their orbits and expelling them. This modelling is in a good agreement with the experimental data.